2019
DOI: 10.3389/fnins.2019.00839
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gut Microbiome in Parkinson’s Disease and the Influence of Lipopolysaccharide in a Human α-Synuclein Over-Expressing Mouse Model

Abstract: The interaction between the gut microbiota and alpha-synuclein (αSyn) aggregation in Parkinson's disease (PD) is receiving increasing attention. The objective of this study was to investigate gut microbiota, and effects of an inflammatory lipopolysaccharide (LPS) trigger in a human αSyn over-expressing mouse model of PD (Thy1-αSyn). Stool samples from patients with confirmed PD and Thy1-αSyn mice were analyzed using 16S ribosomal RNA sequencing. Compared to healthy controls, the relative abundance of mucin-deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(135 citation statements)
references
References 74 publications
(112 reference statements)
6
129
0
Order By: Relevance
“…Elderly patients had no definitive AD, but had decrease in the abundance of anti-inflammatory E. rectale and B. fragilis and increase in abundance of inflammatory taxon Escherichia / Shigella with higher level of IL-1β, CXCL2, NLRP3, and Aβ peptide as compared to healthy controls and subjects with cognitive impairment but had no Aβ pathology [ 95 ]. The changes of gut microbiota and associated immune responses were also showed in Table 1 [ 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ]. It has also been reported that proinflammatory gut bacteria-mediated dysbiosis may induce neuroinflammation and cerebral Aβ accumulation in in AD patients, especially Salmonella , Bacillus , Mycobacterium , E. coli , and Staphylococcus [ 118 ].…”
Section: Interaction Of Gut and Nervous System: Gut–brain Axismentioning
confidence: 99%
See 1 more Smart Citation
“…Elderly patients had no definitive AD, but had decrease in the abundance of anti-inflammatory E. rectale and B. fragilis and increase in abundance of inflammatory taxon Escherichia / Shigella with higher level of IL-1β, CXCL2, NLRP3, and Aβ peptide as compared to healthy controls and subjects with cognitive impairment but had no Aβ pathology [ 95 ]. The changes of gut microbiota and associated immune responses were also showed in Table 1 [ 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ]. It has also been reported that proinflammatory gut bacteria-mediated dysbiosis may induce neuroinflammation and cerebral Aβ accumulation in in AD patients, especially Salmonella , Bacillus , Mycobacterium , E. coli , and Staphylococcus [ 118 ].…”
Section: Interaction Of Gut and Nervous System: Gut–brain Axismentioning
confidence: 99%
“…A recent study showed that the relative abundance of mucin-degrading Verrucomicrobiae and LPS producing Gammaproteobacteria were found to be higher in both PD patients and a human α-synuclein over expressing mice model of PD (Thy-αSyn), as compared healthy and wild-type controls. LPS administration increased the early motor manifestation in Thy-αSyn mice at 10 weeks [ 97 ]. The neuroprotective effect of gut microbiota on MPTP-induced mice model of PD was demonstrated by Reference [ 100 ].…”
Section: Interaction Of Gut and Nervous System: Gut–brain Axismentioning
confidence: 99%
“…Both environmentally [ 244 ] and genetically [ 245 ] induced animal models display altered GM. Depletion of microbiota induced by GF condition or chronic broad-spectrum antibiotics was protective against dopaminergic loss and motor dysfunction in PD mice [ 246 , 247 ].…”
Section: Roles Of Diet and Microbiota In Neurodegenerative Diseasementioning
confidence: 99%
“…LPS administration leads to the increasing of intestinal permeability, motor impairment, nigral a-syn aggregation, dopaminergic neuronal loss and reduction in striatal dopamine. So LPSproducing bacteria increasing can change the gut environment and trigger the pathogenesis of PD by a-syn aggregation (Gorecki et al, 2019). LPS or inflammatory endotoxin modulate a-syn amyloidogenesis by the formation of intermediate nucleating species.…”
Section: Stoolmentioning
confidence: 99%
“…Enterobacteriaceae Gammaproteobacteria LPS Rise the serum LPS population, induce systemic inflammation, promotes a-synuclein deposition, increase LPS-a-syn fibril formation (Guo et al, 2013;Lin et al, 2019;Gorecki et al, 2019;Bhattacharyya et al, 2019)…”
Section: Prevotellaceaementioning
confidence: 99%